Trajetórias de vida de adolescentes do sistema socioeducativo no RN e o envolvimento em facções - Carvalho, Lauriston de Araújo (2020)
In the state of Rio Grande do Norte factions are present in the socio-educational system. The impact of the conflict of these groups on the management of the units and on adolescents, through identity marks of belonging. The present work aimed to analyze the life trajectories of the adolescents interned at Centro Educacional Pitimbu - CEDUC Pitimbu - in the city of Parnamirim / RN, understanding how the links between these trajectories and factions. The data were analyzed from a critical perspective, in the light of historical and dialectical materialism. The results produced show the first signs of the emergence of the factions in the cities of Natal-RN and Parnanamirim-RN, through the relationship with the organized fans (Garra and Mafia) and with a type of individual, novices from the neighborhood, São Paulo accent, tattooed, angry and who walked in groups. These facts show the insertion of these groups in the RN, proximity and admission, as well as the intensification of the conflict in the socio-educational unit. The terrible relationship between adolescents would be motivated by the group differences that originated in the domination of territories in the monopoly disputes of drug trafficking. Adolescents would carry with them the historical legacy of the conflict, stimulated by the neighborhood in which they live, and which is taken into the unit. Living in a certain neighborhood is a condition for joining a faction. Are compulsory affiliations. We also identified that the adolescent from the socio-educational system, their life trajectory is under the influence of social actors, the State, the church faction. The relationships between these actors are not in conflict with each other, but influences that follow through the intertwining of disciplinary devices, in the "pruning" of deviant behaviors. The data also show the ways of acting by the state security forces in the communities of RN, as instruments of poverty management through the new forms of governance of contemporary capitalism. The Mosquito community has a theoretical reference in the State of Permanent Exception, policies of letting die, which address the young, black and poor through the meanings of the criminalization of blackness and poverty. These young people to whom lethality is most strongly affected are the homo sacer, the unworthy of life.